Crowdfunding regulation comparison: Latvia and other Baltic states - Bondarenko, Dmitrijs (Riga Graduate School of Law, 2019)
The main purpose of the thesis is to provide an overview of crowdfunding market and investigate current and potential crowdfunding legal regulation in the Baltic States, as well as to assess in more details current and possible future crowdfunding legal regulation in Latvia in comparison to neighbouring states in the Baltic region.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Baltic states; Fundraising